2020
DOI: 10.3390/cancers12061576
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib Resistance in Hepatocellular Carcinoma: The Relevance of Genetic Heterogeneity

Abstract: Despite advances in biomedicine, the incidence and the mortality of hepatocellular carcinoma (HCC) remain high. The majority of HCC cases are diagnosed in later stages leading to the less than optimal outcome of the treatments. Molecular targeted therapy with sorafenib, a dual-target inhibitor targeting the serine-threonine kinase Raf and the tyrosine kinases VEGFR/PDGFR, is at present the main treatment for advanced-stage HCC, either in a single or combinatory regimen. However, it was observed in a large numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(79 citation statements)
references
References 127 publications
(143 reference statements)
0
79
0
Order By: Relevance
“…As an inhibitor targeting multiple tyrosine protein kinases (VEGFR, PDGFR and Raf family kinases), sorafenib acts on numerous targets to inhibit cancer proliferation and tumor angiogenesis, which can effectively lead to a decrease in mortality in HCC patients. 18 , 19 Advanced stage HCC patients can benefit from 400mg twice daily sorafenib therapy. 5 , 6 , 20 To date, however, clinical trials have revealed that only about 30% patients show sensitivity to sorafenib, and HCC usually progresses within 6 months resulting from resistance to sorafenib.…”
Section: Discussionmentioning
confidence: 99%
“…As an inhibitor targeting multiple tyrosine protein kinases (VEGFR, PDGFR and Raf family kinases), sorafenib acts on numerous targets to inhibit cancer proliferation and tumor angiogenesis, which can effectively lead to a decrease in mortality in HCC patients. 18 , 19 Advanced stage HCC patients can benefit from 400mg twice daily sorafenib therapy. 5 , 6 , 20 To date, however, clinical trials have revealed that only about 30% patients show sensitivity to sorafenib, and HCC usually progresses within 6 months resulting from resistance to sorafenib.…”
Section: Discussionmentioning
confidence: 99%
“…Like most tumors, HCC tumors show heterogeneity [25,26]. After the multiple stages of cell division and proliferation during tumor development, tumor cells undergo various genetic changes, resulting in aberrant growth rate, invasion ability, sensitivity to drugs, and other activities [27].…”
Section: Discussionmentioning
confidence: 99%
“…Possible roles of USP2 in autophagy have also been recently reported. Sorafenib has been used to treat advanced stage hepatocellular carcinoma (HCC) [ 79 ]; however, sorafenib resistance is frequently acquired and is one of the most severe challenges in treating HCC [ 80 ]. A sorafenib-resistant Huh7-derived clone exhibited no obvious activation of caspase-3 and PARP, concomitant with a decreased rate of apoptosis [ 81 ].…”
Section: Apoptosis and Autophagymentioning
confidence: 99%